2018
DOI: 10.7554/elife.39088
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise wiring of the Drosophila olfactory map requires specific Plexin B levels

Abstract: The precise assembly of a neural circuit involves many consecutive steps. The conflict between a limited number of wiring molecules and the complexity of the neural network impels each molecule to execute multiple functions at different steps. Here, we examined the cell-type specific distribution of endogenous levels of axon guidance receptor Plexin B (PlexB) in the developing antennal lobe, the first olfactory processing center in Drosophila. We found that different classes of olfactory receptor neurons (ORNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 63 publications
6
29
0
Order By: Relevance
“…Over the next 6 hours, these two axon bundles circumnavigate the antennal lobe (Figure 2A, left panel). Previously, we found that ORN axon fasciculation is mediated by PlexB-dependent axon-axon interactions (Joo et al, 2013; Li et al, 2018b). In PlexB loss-of-function mutants ( plexB –/– ), ORN axon defasciculation was observed in almost every antennal lobe with differing severity (Figure 2A, middle and right panels; Figure 2B).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Over the next 6 hours, these two axon bundles circumnavigate the antennal lobe (Figure 2A, left panel). Previously, we found that ORN axon fasciculation is mediated by PlexB-dependent axon-axon interactions (Joo et al, 2013; Li et al, 2018b). In PlexB loss-of-function mutants ( plexB –/– ), ORN axon defasciculation was observed in almost every antennal lobe with differing severity (Figure 2A, middle and right panels; Figure 2B).…”
Section: Resultsmentioning
confidence: 98%
“…We previously found that only a small fraction of endogenous PlexB proteins in brains are in a full-length form (Li et al, 2018b), suggesting that cleavage may play a role in tuning PlexB signaling. In the current study, we found that uncleavable PlexB produces more full-length proteins in vivo and possesses higher activity in axon fasciculation and trajectory choice than wild-type PlexB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify molecules underlying Drosophila olfactory-circuit wiring specificity, we previously carried out genetic screens for ORN axon and PN dendrite targeting to the anteriorlateral side of the antennal lobe (11,16). While certain molecules broadly contribute to the precise wiring of many types of olfactory neurons (17,18), others have been found to be region-and even glomerulus-specific (9,11,16,(19)(20)(21). We reasoned that neurons in different locations in the antennal lobe might use a different set of wiring molecules for their circuit assembly.…”
Section: Resultsmentioning
confidence: 99%
“…To identify new molecules underlying the Drosophila olfactory circuit wiring specificity, we have previously carried out genetic screens for ORN axon and PN dendrite targeting to the anterior-lateral side of the antennal lobe (18,19). While certain molecules broadly contribute to the precise wiring of many types of olfactory neurons (20,21), others have been found to be region-and even glomerulus-specific (6,7,11,13,18,22). We reasoned that neurons in different locations in the antennal lobe might use a different set of wiring molecules for their circuit assembly.…”
Section: A Novel Leucine-rich Repeat Protein Fish-lips Is Required mentioning
confidence: 99%